(untitled) (Research, Society and Development, 2020)
Leachate is a highly contaminating liquid generated in landfills, it is one of the main environmental challenges, especially with regard to its treatment, since its varied composition makes it difficult to choose a continuously efficient treatment. Without the proper treatment, it can cause contamination of the soil and surface and underground water resources. In this context, the present study carried out an analysis of the efficiency of the treatment of leachate generated in the landfill in the city of Maceió-AL, verifying its behavior over the years of operation, in addition to possible complications in its treatment. The information was obtained through on-site visits, as well as through secondary data provided by the Superintendency of Urban Cleaning of Maceió (SLUM). As for the treatment of leachate generated in the landfill in Maceió, there were many variations in the efficiencies obtained during the periods, which demonstrates the complexity in the treatment of leachate, especially in a landfill in operation, requiring the adoption of improvements over time. in order to get better results. The biological and coagulation, flocculation and decantation processes provided better performance in the treatment of leachate, obtaining an average global efficiency of 98.79%, 95.45% and 93.42% in removing biochemical oxygen demand (BOD), demand chemical oxygen (COD) and Ammoniacal Nitrogen, respectively.